Pengaruh Label Halal, Kualitas Produk dan Merk terhadap Minat Pembelian Skincare Artha - Suyyinah, Suyyinah; Setiawan, Firman (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Cosmetic products are one of the growing halal beauty products in Indonesia. Currently, the use of cosmetics is almost a primary need for women. The existence of opportunities in the cosmetics industry encourages various halal-labeled cosmetic manufacturers to innovate. This is done by producers to attract interest or meet consumer needs. Based on observations made in Robatal District, Sampang Regency, there is quite a lot of public interest in Skincare Artha, so this research will examine the aspects that influence public interest in Robatal District, Sampang Regency as consumers of Skincare Artha which includes aspects of halal labeling, product quality and brand. This study aims to determine the effect of halal labeling, quality and brand on purchasing Skincare Artha in Robatal District, Sampang Regency, while the independent variables are halal labeling, quality and brand. The data in this study were collected through questionnaires distributed to consumers who have bought and used Artha skincare in Robatal District, Sampang Regency. The research method used is quantitative. The population in this study are people in Robatal District, Sampang Regency who have bought or used Artha's skincare. With the data collected totaling 100 respondents. The data analysis tool used in this study uses multiple linear regression. The results of this study indicate that the halal label, quality and brand variables have a positive and significant effect on the purchase of Artha skincare in Robatal District, Sampang Regency.